2013
DOI: 10.3389/fonc.2013.00260
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Metastatic Disease in Cardiophrenic Lymph Nodes: FDG PET/CT Versus Contrast-Enhanced CT and Implications for Staging and Treatment of Disease

Abstract: Objective: To determine whether FDG PET/CT was more sensitive than CT in detecting metastatic disease in the cardiophrenic space and whether the presence of disease in this location would change the staging and clinical management.Materials and Methods: About 1200 PET/CT scans were retrospectively reviewed over 20 months for the presence of FDG-avid cardiophrenic lymph nodes. The SUVmax was used to quantify the metabolic activity in each of the lymph nodes. The radiographic data was used for correlation. A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The advantage of whole-body PET/CT is that it allows a surgeon to discover suspicious extra- and intra-peritoneal metastases. Farmakis et al found that PET/CT was more accurate than CT alone for identifying CPLNs [ 16 ]. Similarly, Fruscio et al also concluded that PET/CT was a better methodology than CT for detecting distant metastases in AEOC [ 8 ]: PET/CT accurately upstaged 26% of the patients from FIGO stage III to IV during preoperative PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of whole-body PET/CT is that it allows a surgeon to discover suspicious extra- and intra-peritoneal metastases. Farmakis et al found that PET/CT was more accurate than CT alone for identifying CPLNs [ 16 ]. Similarly, Fruscio et al also concluded that PET/CT was a better methodology than CT for detecting distant metastases in AEOC [ 8 ]: PET/CT accurately upstaged 26% of the patients from FIGO stage III to IV during preoperative PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all patients with PET/CT uptake in CPLN in this study— including those who had received NACT—had histologically positive lymph nodes [ 11 ]. Currently, many studies have demonstrated that PET/CT imaging increases the likelihood of finding CPLN metastases, in comparison with CT imaging, especially when they are <10 mm in size [ 26 , 27 , 41 ]. However, another study suggested that CPLN size ≥ 7 mm in a short axis on CT imaging has 85.7% positive predictive value and 58.8% negative predictive value [ 23 ], which is useful in settings where PET/CT is not always available.…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT is more sensitive for detecting involved CPLNs. One retrospective review of 1,200 PET-CT scans obtained from cancer patients over a 20-month period revealed that 9 patients had FDG-avid CPLNs, but only 3 of those 9 had evidence of CPLN involvement on CT scanning [23]. Because our patients were all referred for consolidative RT for HL, stage II disease and bulky involvement were common, which also could account for the higher rate of CPLN involvement.…”
Section: Discussionmentioning
confidence: 99%